A novel positively charged composite nanofiltration membrane based on polyethyleneimine with a tunable active layer structure developed via interfacial polymerization - Jiang, Zhibin; Miao, Jing; He, Yuantao; Tu, Kai; Chen, Shunquan; Zhang, Rui; Zhang, Ling; Yang, Hao (RSC advances, 2019)
A novel positively charged composite nanofiltration (NF) membrane with tunable active layer structure was successfully developed via interfacial polymerization on a polysulfone (PSF) ultrafiltration (UF) membrane surface, using polyethyleneimine (PEI) as the monomer of the aqueous phase, and a mixture of isophthaloyl dichloride (IPC) and tri-mesoyl chloride (TMC) as the monomer of the organic phase. Interestingly, a synergetic effect of the mass ratio of IPC and TMC was observed on the pore size and the structure of the active layer of the resultant polyamide (PA)/polysulfone (PSF) composite NF membrane. The rejection ( R ) to the inorganic electrolytes increased with the mass ratio of IPC to TMC, while the permeate flux ( F ) escalated up to a 1 : 1 mixing ratio of IPC to TMC and dropped at higher mixing ratios. The rejection to different inorganic electrolytes decreased in the order of ZnCl 2 , MgCl 2 , CaCl 2 , CuCl 2 , MgSO 4 , NaCl, and Na 2 SO 4 . At ambient temperature and 0.4 MPa, the optimized membrane demonstrated R and F to 1 g L −1 MgCl 2 aqueous solution as 98.1% and 27.6 L m −2 h −1 , respectively. Its rejection to various dyes reduced significantly in the order of cationic red X-GTL (100%), rhodamine B (94.2%), cationic gold yellow X-GL (93.5%), and brilliant blue KN-R (43.9%), in agreement with the decrease in the molecular weight ( M w ) and the overall charges of the dye.